THE EFFECT OF TWO DIFFERENT METHODS IN TERMS OF MALPRACTICE: A RANDOMİZED CONTROLLED STUDY - Cagla YIGITBAS (Rojan GÜMÜŞ, 2020)
The objective is to research the face-to-face method of education and the educational methods through information technology in the tendency and approach to medical errors and whether some characteristics create a difference on both these situations. It is a randomized controlled intervention research with a pretest-posttest design. A power analysis was carried out and 60 individuals were included in the sampling. Pretesting was conducted through data collection tools before hospital implementations were commenced. The required interventions were conducted after hospital implementations were commenced. No interventions were made on the control group. The individual identificatory characteristics of the participants comprised the independent variables; the Medical Error Tendency Scale for Nurses (METSN) and Medical Error Attitude Scale (MEAS) comprised the dependent variables. The analyses were implemented via SPSS-22 program, and p<0.05 was regarded as the significance level. The mean age of the participants was 22.02 ± 3.33 (20-41). The pretest score from METSN was 217.51 ± 15.14, the posttest score from METSN was 220.18 ± 15.39, the pretest score from MEAS was 62.71 ± 5.24, and the posttest score from MEAS was 64.21 ± 5.18 in terms of Mean ± SD scores. No difference was found in the pretest and posttest scores from METSN and from MEAS of the variables of age group, gender, income, the place lived in over a long period of time, whether the job was selected in accordance with one's own preference, satisfaction with job selection. A moderately positive correlation was found between the pretest and posttest scores from METSN and MEAS. Type of education received and some of the socio-demographic characteristics researched do not constitute any difference in terms of the tendency and attitude to medical error and malpractice; nevertheless, the posttest scores of the intervention groups were high. Evaluation of whether clinical skills make a difference may be recommended